Minor post‐extraction complications other than BRONJ in older patients on oral bisphosphonates – a retrospective study. (19th July 2016) - Lain, Russell; Ajwani, Shilpi
Abstract : Background: Oral bisphosphonates (BP) have been prescribed widely in osteoporosis patients. Bisphosphonate‐related osteonecrosis of the jaw (BRONJ) has been reported as a major complication, but there is little information about minor complications. Objective: This retrospective study describes post‐operative complications – other than BRONJ – associated with dental extractions in patients on oral BP and compares outcomes with patients not on oral BP. Methods: The study period was 2004–05 ending December 2005, prior to the introduction of protocols for minimising risks related to extractions in patients on BP therapy. Records of patients aged 60 years and over who underwent extractions during this period at Sydney Dental Hospital were examined and post‐operative complications analysed. Results: There were 266 participants identified on oral BP therapy out of an available number of 3811 available files based retrospectively from records of 4126 participants who underwent extractions during the two‐year period. In the oral BP group, 10% had complications compared with 2% in the non‐oral BP group ( p < 0.0001). This relationship remained significant even after adjusting for age, gender, operator, type and site of procedure. Delayed healing (36%) and exposed alveolar bone which required an intervention (31%) were the most common complications in the BP group. Conclusion: The prevalence of minor post‐operative complications among BP participants was significantly higher than in non‐BP participants. The nature of the complications was in the range of pathology familiar to – and treatable by – the general dentist.